Corporate governance, intellectual capital, and performance of indonesian public company - Sri Mangesti Rahayu; Wita Ramadhanti (Universitas Hayam Wuruk Perbanas, 2018)
Two important issues for companies’ sustainability are corporate governance and intellectual capital. This research is intended to test the relation between corporate governance, intellectual capital and companies’ performance. This is a quantitative research with archival data. The data is taken from Financial Reports and Annual Reports of Indonesia Public Company during 2011-2016. Corporate governance is measure using proportion of female director and public ownership. Intellectual capital indicators are CEE (Capital Employed Efficiency) and ICE (Intellectual Capital Efficiency). Companies’ performance construct are Tobin’s Q and Return on Assets (ROA) Data then analysed using Partial Least Square. The empirical results is as follows. First, Corporate Governance has positive effect on Intellectual Capital. Second, there is negative effect of Corporate Governance on Performance. Third, Intellectual capital has no effect on firm’s performance. Fourth, Intellectual capital has no mediating effect to the the relation between corporate governance and company’s performance. This results are prove that Agency Theory is the better than Resources Based Theory to explain the Indonesia public companies condition.